Increasing physical activity and sports satisfaction: The role of self-efficacy in physical education for young women - Oktadinata, Alek; Subarjah, Herman; Komarudin,; Hidayat, Yusuf (Journal Sport Area, 2023)
Physical activity is very closely related to movement skills and can be developed through physical education. By integrating self-efficacy into physical education as an intervention, it is hoped that both can be instilled and developed simultaneously.This study aims to examine the effect of self-efficacy in physical education in order to increase physical activity and sports satisfaction for young women. This research is an experimental research using a randomized pretest-posttest control group design. The instruments used to collect data were the International Physical Activity Questionnaire (IPAQ) for young and middle-aged adults (15-59) and the Basic Needs Satisfaction in Sport Scale (BNSSS) instrument to measure satisfaction in sports which were then processed using an independent sample t-test compares two sample means to determine whether the group means differ significantly. The results of this study can be concluded that by integrating self-efficacy content in physical education lessons, it is very large in supporting the physical activities of female students and also increasing students’ motivation and creating a better learning environment. In addition, this intervention can increase satisfaction with physical education learning. These results have an indirect impact on students’ satisfaction in sports. Furthermore, it is necessary to conduct research on samples from various regions and samples of elementary school and college students.